Mutation Patterns of the Reverse Transcriptase and Protease Genes in Human Immunodeficiency Virus Type 1-Infected Patients Undergoing Combination Therapy: Survey of 787 Sequences - Yahi, Nouara (American Society for Microbiology, 1999)
The aim of the present study was to evaluate the resistance-associated mutations in 302 human immunodeficiency virus type 1 (HIV-1)-infected patients receiving combination therapy and monitored in Marseille, France, hospitals from January 1997 to June 1998. In the reverse transcriptase (RT) gene, the most frequent mutations were found at codons 215 (53%), 41 (34%), and 67, 70, 184, and 210 (>20%). One deletion and two insertions in the β3-β4 hairpin loop of the finger subdomain (codon 69) were detected. Interesting associations and/or exclusions of specific mutations were observed. In 96% of RT genes, a mutation at codon 70 (most frequently, K70R) was associated with a wild-type genotype at position 210 (P < 10(−5)). Similarly, a mutation at codon 210 (most frequently, L210W) was generally associated with mutations at codons 41 (92%) and 215 (96%) but not at codon 219 (16%) or codon 70 (4%) (P < 10(−5)). In the protease gene, the most prevalent mutations were at codons 63 (84%), followed by codons 10, 36, 71, 77, and 93 (ca. 20%). As for RT, pairwise associations of mutations were observed. Analysis of the mutation patterns for patients with undetectable HIV-1 loads revealed a high proportion (65%) of wild-type RT genotypes but only 18% wild-type protease genotypes. For patients with high viral loads (>100,000 copies/ml), more than 50% of the RT and protease genes displayed three or more mutations. The significant correlation between the level of viremia in plasma and the number of resistance mutations in the protease (P = 0.007) and RT (P = 0.00078) genes strengthens the importance of defining the genotype of the predominant HIV-1 quasispecies before initiating antiretroviral therapy.